Evolution of the big deals use in the public universities of the Castile and Leon region, Spain - Fernández-Ramos, Andrés, (El Profesional de la información, 2019)
The evolution of the use of electronic scientific journals in the 2007-2018 period by the academic communities of the public universities of Castilla and Leon, members of the Bucle consortium, is studied. Downloads of articles distributed by four broad-spectrum providers are analyzed: Emerald, ScienceDirect, SpringerLink, and Wiley. Unexpectedly, in spite of the new ways of accessing content, this analysis shows that the number of downloads in public universities in Castile and Leon has increased. However, it has been found that despite the growth, a few journals concentrate most of the downloads and that a large number of titles are not used. It has been verified that the universities with a higher number of staff and greater diversity of knowledge areas use a wider range of titles and thus obtain a higher benefit from their contracts. All of the above leads us to question the system of contracting big deals, i.e., bundles of hundreds of multidis ciplinary journals and other resources. In a moment of change promoted by Plan S, we consider it more necessary than ever to understand the situation of the provision of serial scientific publications and to find the best strategy to have access to them.